PENGARUH KEDISIPLINAN, MOTIVASI, DAN PENGEMBANGAN DIRI TERHADAP KINERJA ASN PADA BADAN PENGELOLA KEUANGAN DAN ASSET DAERAH KABUPATEN MAMUJU - Ramadhan, Adam; Rahim, Abdul Rahman; Rum, Muhammad (UNIVERSITAS MUHAMMADIYAH MAKASSAR, 2020)
The design of this research is descriptive quantitative to determine the effect of discipline, motivation, and self-development on the performance of the state civil apparatus in the Financial Management Agency and Regional Assets in the Province of West Sulawesi. The study population is all state civil servants who work at the Regional Financial and Asset Management Agency of Mamuju Regency with a population of 62 people, by sampling method applied because the total population is less than 100, then the entire population becomes the study sample. The time of the study was carried out for 3 months, start from April to July 2019. Using primary data sources with ordinal data scales measured on a Liker’s scale, with technical analysis in multiple regression analysis. The results of this study indicate that simultaneously indicated by the results of the F test, that discipline, motivation, and self-development affect employee performance. Partially it is also shown by the t-test results that discipline, motivation, and self-development partially affect employee performance, with motivation being the dominant variable influencing employee performance. Keywords: Discipline, Motivation, Personal Development, State Civil Apparatus Performance